A Study of Universal Thermodynamics in Brane World Scenario. (19th January 2015) - Mitra, Saugata; Saha, Subhajit; Chakraborty, Subenoy
Abstract : A study of Universal thermodynamics is done in the framework of RSII brane model and DGP brane scenario. The Universe is chosen as FRW model bounded by apparent or event horizon. Assuming extended Hawking temperature on the horizon, the unified first law is examined for perfect fluid (with constant equation of state) and Modified Chaplygin Gas model. As a result there is a modification of Bekenstein entropy on the horizons. Further the validity of the generalized second law of thermodynamics and thermodynamical equilibrium are also investigated.